Membranoproliferative Glomerulonephritis and X-Linked Agammaglobulinemia: An Uncommon Association. (4th March 2014) - Lavrador, Vasco; Correia, Filipa; Sampaio, Rita; Cândido, Cristina; Sameiro-Faria, Maria; Marques, Laura; Mota, Conceição
Abstract : Introduction . X-linked agammaglobulinemia (XLA) is a primary immunodeficiency characterized by agammaglobulinemia requiring replacement treatment with immunoglobulin. The association of XLA and membranoproliferative glomerulonephritis (MPGN) is unexpected and, to our knowledge, only one case was previously published. Case Report . The authors report the case of a 10-year-old boy with family history and prenatal diagnosis of XLA, treated from birth with intravenous immunoglobulin replacement therapy. He presented with pneumonia, macroscopic hematuria, nephrotic proteinuria, hypoalbuminemia, and hypercholesterolemia with normal renal function and serum complement levels. Renal histology showed immune complex mediated MPGN. He was started on high dose prednisolone and ramipril and switched to weekly subcutaneous immunoglobulin. After a 4-month treatment, hematuria and proteinuria significantly improved and prednisolone was gradually tapered without relapse. Conclusion . The pathogenic process underlying MPGN development in this patient is unknown but residual humoral immunity might play an important role. Thus, this case highlights the risk of autoimmune disorders among patients with XLA.